2007
DOI: 10.1117/1.2757707
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral data noise characterization using principle component analysis: application to the atmospheric infrared sounder

Abstract: Exploiting the inherent redundancy in hyperspectral observations, Principle Component Analysis (PCA) is a simple yet very powerful tool not only for noise filtering and lossy compression, but also for the characterization of sensor noise and other variable artifacts using Earth scene data. Our approach for dependent set PCA of radiance spectra from the Atmospheric Infrared Sounder (AIRS) on NASA Aqua is presented. Aspects of the analyses include 1) estimation of NEDT and comparisons to values derived from on-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…The authors in [7] applied a PCA-based noise filter, which eliminates the higher order principal components, to reduce the random noise present in the simulated and real hyperspectral infrared observations. The authors in [8] showed that the PCA is a powerful technique for diagnosing and filtering Atmospheric Infrared Sounder (AIRS) noise and other variable artifacts in hyperspectral data. The author in [9] also used the PCA approach to remove the subtle distortions in the AIRS instrument line shape introduced by nonuniform scene effects.…”
Section: Fengyun-3b Microwave Humidity Sounder (Mwhs) Data Noise Charmentioning
confidence: 99%
“…The authors in [7] applied a PCA-based noise filter, which eliminates the higher order principal components, to reduce the random noise present in the simulated and real hyperspectral infrared observations. The authors in [8] showed that the PCA is a powerful technique for diagnosing and filtering Atmospheric Infrared Sounder (AIRS) noise and other variable artifacts in hyperspectral data. The author in [9] also used the PCA approach to remove the subtle distortions in the AIRS instrument line shape introduced by nonuniform scene effects.…”
Section: Fengyun-3b Microwave Humidity Sounder (Mwhs) Data Noise Charmentioning
confidence: 99%
“…An example of the use of local rather than global training sets is the production of 'granule-based' principal components with AIRS data (Antonelli et al, 2004;Tobin et al, 2007). Here a granule is made up of six minutes of AIRS observations.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Moreover, our study found that the use of a smaller set of the PCs as the predicators can effectively reduce the bias at extreme OLR values (>310 Wm −2 ). The biases at high OLR values may be related to AIRS's scene‐dependent instrumental noise at shortwave spectral range [ Tobin et al , 2007].…”
Section: Technique For Estimation Of Airs Outgoing Longwave Radiationmentioning
confidence: 99%